PREPARATION AND CHARACTERISATION OF BORA RICE ACECLOFENAC MICROSPHERES - SUNITA, LAHKAR (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Â  Objective: The present research work is based on the applicability of bora rice as a natural polymer for preparing sustained aceclofenac bora rice microspheres. Methods: The microspheres were prepared by emulsion solvent diffusion technique.â€ The physicochemical characterizations of the prepared microspheres (percentage drug entrapment efficiency, scanning electron microscopy, percentage drug loading) were carried out as well as the in vitro drug release was carried out in phosphate buffer pH 6.8. Result: The prepared microspheres were found to have a regular spherical shape, percentage drug entrapment efficiency of 52.6%. The in vitro release study in phosphate buffer pH 6.8 showed a sustained release of the drug for 24 hrs. Conclusion: The bora rice as a natural biodegradable polymer could efficiently sustained the release of aceclofenac for 24 hrs. Keywords: Bora rice, Aceclofenac, Scanning electron microscope, Sustained release.